Weakly-correlated nodeless superconductivity in single crystals of Ca3Ir4Sn13 and Sr3Ir4Sn13 revealed by critical fields, Hall effect, and magnetoresistance measurements - L M Wang; Chih-Yi Wang; Guan-Min Chen; C N Kuo; C S Lue (New Journal of Physics, 2015)
We report a study of single crystal Ca _3 Ir _4 Sn _13 (CIS) and Sr _3 Ir _4 Sn _13 (SIS) by measuring the longitudinal and Hall resistivities, upper and lower critical fields and magnetoresistance, as well as the magnetization. The sign change in the Hall coefficient observed on both the CIS and SIS provides direct evidence for the Fermi surface reconstructing during the superlattice phase transition. Both materials are of current interest due to indications of superconductivity associated with charge-density-wave (CDW) ordering. Observations of the diamagnetic feature and the lower critical field H _c _1 ( T ) in both CIS and SIS can be realized by means of the nodeless single-gap BCS theory. In addition, a weak electronic correlation in both systems has been revealed by the small values of the spin exchange energy, upper critical field and Δ (0)/ k _B T _c ratio, derived respectively from the normal-state Hall effect, resistive transition and temperature-dependent H _c _1 . It is noticeable that the magnetoresistance of SIS shows a rapid increase below T′  ∼ 40 K, following Kohler’s scaling rule. The results of the magnetic susceptibility and Hall coefficient also exhibit anomalous features near T′ . With respect to these observations, this suggests that the existence of an additional phonon mode with energy of about 4.0 meV in SIS is responsible for the presence of lattice instability toward a phase transition.